2021
DOI: 10.1155/2021/8827206
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Prevalence and Identification of Ehrlichia canis and Anaplasma platys from Dogs in Nay Pyi Taw Area, Myanmar

Abstract: Ticks are vectors of different types of viruses, protozoans, and other microorganisms, which include Gram-negative prokaryotes of the genera Rickettsiales, Ehrlichia, Anaplasma, and Borrelia. Canine monocytic ehrlichiosis caused by Ehrlichia canis and canine cyclic thrombocytopenia caused by Anaplasma platys are of veterinary importance worldwide. In Myanmar, there is limited information concerning tick-borne pathogens, Ehrlichia and Anaplasma spp., as well as genetic characterization of these species. We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Non-specific signs, fever, anemia, anorexia, dullness, and thrombocytopenia [5] Morulae in stained blood smear, thrombocytopenia, leucopenia, elevated liver enzymes, serology, andPCR/DNA sequencing [1,5] Doxycycline 5 mg/kg bid for 28 days [172] Vector control, habitat modification, rearing tick-resistant breeds, and chemotherapy [5] Human granulocyticanaplasmosis Fever, headache, myalgias, and chills [123] Morulae in stained blood smear, thrombocytopenia, leucopenia, elevated liver enzymes, serology/IFA, and PCR/DNA sequencing [95,173] Doxycycline @ 100 mg, orally, twice dailyfor 10-14 days or rifampicin @ 20 mgkg −1 day −1 orallyfor children, otherwise 300 mg orally, twice dailyfor 5-7 days [47] Humans: Minimizing high-risk tick exposure activities (hiking, gardening, etc. ), blood transfusion, immune suppression, identificationof reservoirs and vectors, and their control [1]…”
Section: Canine Granulocytic Anaplasmosismentioning
confidence: 99%
“…Non-specific signs, fever, anemia, anorexia, dullness, and thrombocytopenia [5] Morulae in stained blood smear, thrombocytopenia, leucopenia, elevated liver enzymes, serology, andPCR/DNA sequencing [1,5] Doxycycline 5 mg/kg bid for 28 days [172] Vector control, habitat modification, rearing tick-resistant breeds, and chemotherapy [5] Human granulocyticanaplasmosis Fever, headache, myalgias, and chills [123] Morulae in stained blood smear, thrombocytopenia, leucopenia, elevated liver enzymes, serology/IFA, and PCR/DNA sequencing [95,173] Doxycycline @ 100 mg, orally, twice dailyfor 10-14 days or rifampicin @ 20 mgkg −1 day −1 orallyfor children, otherwise 300 mg orally, twice dailyfor 5-7 days [47] Humans: Minimizing high-risk tick exposure activities (hiking, gardening, etc. ), blood transfusion, immune suppression, identificationof reservoirs and vectors, and their control [1]…”
Section: Canine Granulocytic Anaplasmosismentioning
confidence: 99%
“…However, some studies report a rather low prevalence of E. canis (Malaysia -2%, Myanmar -0.75%, etc. ), or even fail to detect the presence of E. canis in the studied dog population (Croatia) [10,29,30]. The established differences in the prevalence of E. canis in different studies are mainly infl uenced by the wide variety of approaches used for the study design.…”
Section: Resultsmentioning
confidence: 99%
“…Several other closely related Ehrlichia have been identified in other studies reported from Africa and Asia, so this Ehrlichia lineage may be distributed very broadly. Ehrlichia canis and Anaplasma platys have been reported in different parts of India and other southeastern Asian countries, [67][68][69][70] but their presence in Sri Lanka is unknown. Further work is required to perform more in-depth analyses of these yet-uncultured Ehrlichia genotypes, and, most importantly, to determine their potential to cause human and veterinary diseases.…”
Section: Discussionmentioning
confidence: 99%